TATA KELOLA KEUANGAN KOPERASI DINAR AMANTA MELALUI PENERAPAN TEKNOLOGI SISTEM INFORMASI - Dina Dwi Oktavia Rini; Aisha Hanif; Ika Ratna Indra Astutik (Jurnal Abdimas Bina Bangsa, 2023)
The Dinar Amanta Cooperative faces many challenges and problems. The classic problems that are commonly faced by cooperatives are the problem of capital to develop the business, as well as the competence of the management to carry out accountable financial governance in compiling financial reports which is still relatively low. In addition, cooperative management that has not been carried out effectively through computerized processes in its operational activities is also a problem and a challenge for the business continuity of the Dinar Amanta Cooperative. The approach method used to overcome problems from partners is (1) counseling and training related to cooperative financial management so that it is in accordance with applicable accounting standards, (2) making cooperative financial management application programs and holding demonstrations, and (3) training in using the program cooperative financial governance application. The fundamental contribution to the target audience is the increased understanding and competency of the Amanta Dinar Cooperative management regarding cooperative financial management in accordance with applicable accounting standards and can be accounted for, encouraging the Amanta Dinar Cooperative to become an effective savings and loan cooperative in its business activities, and the creation of a Dinar Cooperative financial application program Amanta